Clinical-genealogical study of patients with chronic obstructive pulmonary disease - G. N. Seitova; S. A. Bogushevich; E. A. Dementjeva; S. V. Nesterovich; E. B. Bukreeva (Бюллетень сибирской медицины)
We present data of clinical-genealogical study of patients with chronic obstructive bronchitis (82 people) and control group (108 people). Study of frequency of lung’s disease in parents and relatives of seek patients and patients from control group revealed the prevalence of bronchopulmonary pathology in the first group in comparison with the second. Study of frequency morbidity depending on the gender of descendents determined the significant prevalence in girls than in boys. Study of type of family burdening in seek patients revealed the prevalence of the type «seek mother, healthy father».